Adaptive responses of biofortified common bean lines to acidic soil and high temperatures in the Colombian Amazon region - Suárez, Juan Carlos; Contreras, Amara T.; Urban, Milan O.; Grajales, Miguel A.; Beebe, Stephen Edgar; Rao, Idupulapati M. (MDPI, 2024)
One of the strategies to combat micronutrient malnutrition is by developing biofortified common bean lines (Phaseolus vulgaris L.) capable of tolerating different stress conditions. In this study, the adaptive responses of different biofortified bean lines grown under combined stress of acidic soil and high-temperatures were evaluated in the Colombian Amazon. A total of 247 common bean lines from the Mesoamerican gene pool were used to determine the adaptive response in terms of phenological, physiological, and agronomic behavior under combined stress conditions. The lines tested were obtained from different single crosses, double crosses, and backcrosses between different bean materials, of which 146 were obtained from F4 families with high iron (Fe) content in seed and 99 common bean lines from F5 families. Different bean lines had grain yields (GY) higher than 1400 kg ha−1 from the F5 (lines: 859, 805, 865, and 657) and F4 (lines: 2853 and 2796) families. The superior performance of these lines was related to a higher photosynthate partitioning that has allowed an increase in pod formation (pod partitioning index, PPI) from the canopy biomass (CB) and grain filling (pod harvest index, PHI; harvest index, HI), resulting in higher values of GY. Values of GY were correlated with CB (r = 0.36), PPI (r = 0.6), PHI (r = 0.68), and HI (r = 0.8, p < 0.001). This increase in agronomic performance is due to a greater allocation of energy to the photosynthetic machinery (ΦII) and its dissipation in the form of heat (ΦNPQ), with increases in the leaf temperature difference (LTD). Based on the results obtained, six biofortified lines of common bean (lines F5: 859, 805, 865, and 657; lines F4: 2853 and 2796) showed traits of tolerance to combined stress and can serve as progenitors to increase Fe and Zn concentration in the seeds of lines that tolerate the combined stress from acidic soil and high temperature in the Colombian Amazon region.